1993
DOI: 10.1073/pnas.90.4.1526
|View full text |Cite
|
Sign up to set email alerts
|

Pigment epithelium-derived factor: neurotrophic activity and identification as a member of the serine protease inhibitor gene family.

Abstract: Cultured pigment epithelial cells of the fetal human retina secrete a protein, pigment epithelium-derived factor (PEDF), that induces a neuronal phenotype in cultured human retinoblastoma cells. Morphological changes include the induction of an extensive neurite meshwork and the establishment of corona-like cellular aggregates surrounding a central lumen. The differentiated cells also show increases in the expression of neuron-specific enolase and the 200-kDa neurofilament subunit. Amino acid and DNA sequence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
315
0
4

Year Published

1996
1996
2004
2004

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 418 publications
(323 citation statements)
references
References 14 publications
(18 reference statements)
4
315
0
4
Order By: Relevance
“…1,2 It shares high sequence homology with other serine proteinase inhibitors (serpins) and behaves like a noninhibitory serpin. 3 PEDF is found in a broad range of human fetal and adult tissues, including almost all brain areas. 4 Later studies have demonstrated that it can promote the survival of cerebellar granule cells (CGCs), 5 induce differentiation in retinoblastoma tumor cells in vitro, 6 and protect retinal neurons from apoptotic death.…”
mentioning
confidence: 99%
“…1,2 It shares high sequence homology with other serine proteinase inhibitors (serpins) and behaves like a noninhibitory serpin. 3 PEDF is found in a broad range of human fetal and adult tissues, including almost all brain areas. 4 Later studies have demonstrated that it can promote the survival of cerebellar granule cells (CGCs), 5 induce differentiation in retinoblastoma tumor cells in vitro, 6 and protect retinal neurons from apoptotic death.…”
mentioning
confidence: 99%
“…Pigment epithelium-derived factor (PEDF), a 418-aa 50-kDa glycoprotein, is a member of the serine protease inhibitor (serpin) family (10,11). Although PEDF has a putative proteasesensitive loop, unlike classical serpins such as ␣1-antichymotrypsin (ACT), PEDF lacks protease inhibitory activity.…”
mentioning
confidence: 99%
“…The retinal pigment epithelium (RPE) is a highly specialized neuroepithelium, which develops in advance of and lies adjacent to the interphotoreceptor matrix. The RPE, which plays a critical role in retinal homeostasis, synthesizes and secretes many soluble products into the interphotoreceptor matrix, among them PEDF, [8][9][10] a 50-kDa member of the serpin (serine protein inhibitor) family. PEDF is expressed intracellularly in almost all human ocular tissues and extracellularly during both foetal and early adult periods.…”
Section: Discussionmentioning
confidence: 99%
“…PEDF is expressed intracellularly in almost all human ocular tissues and extracellularly during both foetal and early adult periods. [8][9][10]31 It is also expressed by cells other than RPE, such as cultured foetal lung fibroblasts, where its downregulation is linked to the process of senescence. 32 PEDF has been detected in the eyes of human fetuses at 17 weeks of gestation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation